2020
DOI: 10.1063/5.0022310
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear forced vibration of bilayer van der Waals materials drum resonator

Abstract: The interlayer shear effect could play a crucial role in the dynamic behaviors of the nanoelectromechanical system (NEMS) resonators based on multilayer van der Waals (vdW) materials. However, the interlayer shear effect is rarely considered in the nonlinear forced vibrations of this kind of resonators. In this study, the nonlinear static and dynamics behaviors of drum resonators based on double layer MoS2 (DLMoS2) are investigated using molecular dynamics simulations and a nonlinear circular sandwich plate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…From Eqs. (17) and (18) we can see that the oscillator's self-oscillation amplitude is govered by the quality factor Q, nonlinearity β, feedback force f 0 and phase delay φ 0 (the perturbation strength f s is small enough, i.e. |A−A0| A0 ≈ 0).…”
Section: Synchronization Bandwidth With Phase Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…From Eqs. (17) and (18) we can see that the oscillator's self-oscillation amplitude is govered by the quality factor Q, nonlinearity β, feedback force f 0 and phase delay φ 0 (the perturbation strength f s is small enough, i.e. |A−A0| A0 ≈ 0).…”
Section: Synchronization Bandwidth With Phase Delaymentioning
confidence: 99%
“…Microelectromechanical systems (MEMS) have increasingly attracted considerable interest due to their small size and low power consumption since the integrated circuit (IC) technology rise in 1990. Related investigations not only focus on fundamental questions, such as frequency locking [28,26,27], internal resonance [7,20,41], mode coupling [4,29,9], pull-in [14,43], exit time [42], bilayer effect [17], etc., but also in tremendous potential applications including gas/mass sensing [12,34,33], filters [1], memory devices [39] and time keeping [3]. Due to the size effect, MEMS system is easily driven into nonlinear regime.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] As Vg increases to 2 V, the resonance peak changes to an asymmetric one from a symmetric line shape, confirming the Ti 3 C 2 Tx MXene resonator has become the nonlinear regime. [ 40 , 41 ] In this case, it can be described using the Duffing resonator model with an effective additional term and , which is related to the nonlinear restoring force and nonlinear damping, [ 2 ] and the detailed derivation is shown in the Part S8 , Supporting Information. The stable state of the Duffing equation is described as [ 7 ] where x is the motional amplitude, k is the effective spring constant, m is the resonator mass, γ is the linear damping coefficient, η is the nonlinear damping coefficient, α is the Duffing force coefficient, F 0 is the amplitude of the driving force, ω is the driving frequency, and t is time.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the two in-plane directions being anisotropic, the mechanical properties are also out of plane anisotropy for multilayer BP due to the weak interlayer van der Waals (vdW) interactions but remain less well investigated. A critical factor determining the overall performance of multilayer 2D materials lies in the interlayer vdW interactions [25][26][27][28]. For example, Zhang et al [25] found that a positive shear modulus can increase the natural frequency for multilayered BP by MD simulations and continuum modelling.…”
Section: Introductionmentioning
confidence: 99%